Oxygen uptake efficiency slope calculations based on heart rate reserve endpoints in young, intellectually disabled individuals - Tamotsu Yabumoto; Reizo Baba; Tsuneo Watanabe; Naoki Sakakibara; Takeshi Ukai; Osamu Fukutomi; Toshio Matsuoka (Japanese Society of Physical Fitness and Sports Medicine, 2012)
The validity of a new methodological approach, involving the use of exercise endpoints based on fractions of heart rate reserve (HRres), to calculate oxygen uptake efficiency slopes (OUES) was tested. The study involved 48 young, intellectually disabled individuals (age range: 15-17 years) who performed an incremental cycling exercise to exhaustion. Furthermore, regarding the subjects who reached maximum efforts, the relationship between OUES and several exercise performance parameters was assessed. OUES was calculated using 75%, 90%, and 100% of the incremental exercise with data and data corresponding to 60% and 80% of the HRres. Of the 48 participants, 12 subjects did not reach a peak RER of 1.09, and 36 subjects exceeded this value. Significant differences were not detected between the time-based calculations and those obtained using the HRres-based measures of OUES. A Bland-Altman analysis did not reveal a bias that was significantly different from 0 (15.5 and 68.6 for OUES80%HRres-OUES100 and OUES60%HRres-OUES100, respectively), with precisions of 173.2 and 356.0 and 95% confidence limits from -296.8 to +327.8 and from -507.1 to +644.3 for OUES80%HRres-OUES100 and OUES60%HRres-OUES100 comparisons, respectively. High correlations were detected between peak oxygen uptake and OUES60%res and OUES80%HRres, and between VT and OUES60%res and OUES80%HRres. Thus, we found that OUES can be reliably calculated based on HRres endpoints, during incremental cycling exercise, in young individuals with intellectual disabilities. Furthermore, the study confirms the validity of OUES as an indicator of aerobic exercise capability in this population.